Public-Private Partnerships on Water and Sanitation Issues in Small Towns: Case of Mvurwi, Zimbabwe - Mark Makomborero Matsa; Tatenda Musasa; Rameck Defe (Springer Nature Switzerland, 2022)
The study examined the role of public–private partnerships in solving water and sanitation issues affecting Mvurwi town. A total of 144 question- naires were administered to respondents across Suwoguru, Rusununguko Phase 2, and Pembi View. Purposive sampling was employed to select key participants such as the Town Secretary, and Community Services Clerk. The Statistical Pack- age for Social Sciences Version 20.0 software was used to analzse data. Findings indicate that 66% of the respondents are directly affected by water and sanitation issues. Fifty percent of the respondents agree that public–private partnerships are essen- tial in rehabilitating the water and sanitation sector in Mvurwi.